Pelatihan Pembuatan Bolu Ampas Tahu Lokal di Kelurahan Lewirato - Muhammad Rizki Bima Putra; Ratu Syafira Nurasyifa; Mely Sukma Dewi Ratu Mutiara; Nurlayli Istiqomah; Merlin Qhardanova; Sri Rezeki; Nunung Faujiah; Isti Mulyati; Zyad Dilmi (Indonesia Bergerak : Jurnal Hasil Kegiatan Pengabdian Masyarakat, 2024)
Tofu dregs cake is increasingly becoming a favorite among the community, creating opportunities for mothers in Lewirato Village to develop it as a home industry. This research reviews entrepreneurship training efforts aimed at teaching mothers how to make tofu dregs cake, with the aim of increasing skills and local economic potential. The implementation method involves demonstration, direct observation, and interviews. This training was carried out involving women from PKK cadres and households around the sub-district. The results showed an increase in skills in making tofu dregs sponge cake and high enthusiasm from the participants. In conclusion, this activity empowers mothers to produce quality tofu dregs cake, reduces dependence on external purchases, and strengthens the local economy.